PENGARUH MODEL PAIR CHECK TERHADAP KECERDASAN INTERPERSONAL SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SDN KELURAHAN KEMBANGAN UTARA - Ramadhani, Nur Syadida; Satibi Hidayat, Otib; Chandra Muji Utami, Nidya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the pair check model on students' interpersonal intelligence in the Pancasila Education in grade V of elementary school. The main focus of this research is to analyze the level of interpersonal intelligence. The research method used a quasi-experimental design in the form of a Nonequivalent Control Group Design. Two classes were used in the research sample, the experimental class using the Pair Check model and the control class using the Think Pair Share model. The research data comes from a self-assessment questionnaire and peer-assessment questionnaire that assesses the social insight aspect of interpersonal intelligence. The results of the study an increase in the average score of the experimental class reaching 56.53% with the category "Quite Effective", while the control class experienced an increase of 23.05% with the category "Not Effective". The hypothesis used the Independent sample t-test which showed a significance value (2-tailed) of 0.000 < 0.05, which means there is a difference between the two classes. Thus, it is concluded that the use of Pair Check model has a significant effect on increasing interpersonal intelligence in the Pancasila Education of fifth-grade elementary school students.